Antioxidant and antimicrobial properties of two local edible mushrooms / Wan Elyn Amira Wan Adnan - Wan Adnan, Wan Elyn Amira (Faculty of Applied Sciences, 2009)
This study was carried out to compare the antioxidant and antimicrobial properties of some selected mushrooms, Lentuinula edodes (shitake mushroom) and Pleurotus sajorcaju (grey oyster mushroom). The mushrooms were extracted using ethanol. The antioxidant properties is detected using total phenolic compound assay, free radical scavenging activity (DPPH) and ferric reducing power activity (FRAP) assays. Disk diffusion method was used to determine the antimicrobial properties of Lentuinula edodes and Pleurotus sajorcaju. Total phenolic compound are natural antioxidant components found in the ethanolic extracts of Lentuinula edodes and Pleurotus sajorcaju were 10.71 and 0.542 µgGAE/mg respectively. The reducing power of mushroom species and standard used followed in the decreasing order of BHA/BHT > Ascorbic acid > Lentuinula edodes > Pleurotus sajorcaju. The free radical scavenging activity of mushroom species and standards were decreased in the order of BHA/BHT > Ascorbic acid > Pleurotus sajorcaju > Lentuinula edodes. The reactivity of antimicrobial properties Lentuinula edodes and Pleurotus sajorcaju were investigated against selected microorganisms such as S. aureus (gram positive), B. subtilis (gram positive), P. aeruginosa (gram negative), E. coli (gram negative), C. albicans (mould and yeast) and A. niger (mould and yeast). Generally, Lentuinula edodes and Pleurotus sajorcaju have moderately antimicrobial properties against all selected microorganisms except A. niger.